Applied Network Science - Menezes, Ronaldo; Cherifi, Hocine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Applied Network Science (ANS) is an open-access and strictly peer-reviewed journal giving researchers and practitioners in the field the ability to reach a larger audience. ANS encompasses all established and emerging fields that have been or can be shown to benefit from quantitative network-based modeling. Contributions from all fields of science, technology, medicine and humanities will be considered, in particular from newly emerging research areas formed and developing at the interfaces of presently established sub-disciplines. The focus of the journal is based on novel or anticipated applications of network sciences, on related techniques that may be used in applications of complex network methodologies, and on innovative modeling approaches that will enhance specific applications and lead to more widespread use of network science concepts. Overall, articles that have a direct application to real world problems form the core publications of this journal.
Keywords: Physics; Computer simulation; Complexity, Computational; Physics; Applications of Graph Theory and Complex Networks; Complexity; Simulation and Modeling